(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
A synchronic and diachronic study of gender lexical units in English and Uzbek involves examining the usage and development of words and phrases related to gender both in their current state (synchronic) and over time (diachronic). This comprehensive approach allows for a deeper understanding of how gender-related language has evolved and continues to shape and be shaped by social and cultural contexts.